Implementation of Media Richness Theory in the Use of Microsoft Teams Applications - Yasindy Risma Hani; Dewi Maria Herawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This journal article reviews the literature on the implementation of communication theory in the use of Microsoft Teams applications which aims to see the user's perspective in communicating through Microsoft's flagship application, Microsoft Teams. This study aims to determine the implementation of media richness theory in the use of Microsoft Teams applications. Which includes the experience of informants when using the Microsoft Teams application in their daily lives. This study uses qualitative research methods, using the theory of media richness which looks at the stages or the highest level of communication, namely directly (face-to-face). Data collection techniques using observation, interviews and documentation. Based on researcher interviews with informants, the Microsoft Teams application can be a media solution or media support for work productivity and education, especially in terms of interaction and communication with other users. However, Microsoft Teams also has some drawbacks that make this video conferencing application not equivalent to face-to-face communication.